High Titer and Avidity of Nonneutralizing Antibodies against Influenza Vaccine Antigen Are Associated with Severe Influenza - To, Kelvin K. W. (American Society for Microbiology, 2012)
The importance of neutralizing antibody in protection against influenza virus is well established, but the role of the early antibody response during the initial stage of infection in affecting the severity of disease is unknown. The 2009 influenza pandemic provided a unique opportunity for study because most patients lacked preexisting neutralizing antibody. In this study, we compared the antibody responses of 52 patients with severe or mild disease, using sera collected at admission. A microneutralization (MN) assay was used to detect neutralizing antibody. We also developed an enzyme-linked immunosorbent assay (ELISA) which detects both neutralizing and nonneutralizing antibodies against viral antigens from a split-virion inactivated monovalent influenza virus vaccine. While the MN titers were not significantly different between the two groups (P = 0.764), the ELISA titer and ELISA/MN titer ratio were significantly higher for patients with severe disease than for those with mild disease (P = 0.004 and P = 0.011, respectively). This finding suggested that in patients with severe disease, a larger proportion of serum antibodies were antibodies with no detectable neutralizing activity. The antibody avidity was also significantly higher in patients with severe disease than in those with mild disease (P < 0.05). Among patients with severe disease, those who required positive pressure ventilation (PPV) had significantly higher ELISA titers than those who did not require PPV (P < 0.05). Multivariate analysis showed that the ELISA titer and antibody avidity were independently associated with severe disease. Higher titers of nonneutralizing antibody with higher avidity at the early stage of influenza virus infection may be associated with worse clinical severity and poorer outcomes.